Chloromonas svalbardensis n. sp. with Insights into the Phylogroup Chloromonadinia (Chlorophyceae). (5th June 2018) - Barcytė, Dovilė; Hodač, Ladislav; Nedbalová, Linda; Elster, Josef
Abstract: The traditional green algal genus Chloromonas accommodates mesophilic, cold‐tolerant and cold‐adapted microorganisms. In this paper, we studied a new strain isolated from a wet hummock meadow in the High Arctic. We used morphological, ultrastructural and molecular data to assess the taxonomic position and phylogenetic relationships of the new isolate. The observed morphological features generally corresponded to the cold‐tolerant Chloromonas characteristics. However, ellipsoidal or wide ellipsoidal vegetative cells, a massive parietal cup‐shaped chloroplast with a number of continuously connected lobes, a thick cell wall, a prominent hemispherical papilla and the anterior position of an oblong or round eyespot distinguished the alga from all previously described Chloromonas species. Analyses of rbc L and 18S rRNA genes showed that the new strain formed an independent lineage within a clade containing mesophilic and psychrotolerant Chloromonas species. Comparisons of secondary structure models of a highly variable ITS2 rDNA marker supported a separate species identity of the new isolate. Considering the morphological and molecular differences from its relatives, a new psychrotolerant species, Chloromonas svalbardensis, is proposed. Further, our results demonstrated the paraphyletic origin of Chloromonas within Chloromonadinia with genetically, morphologically and ecologically well‐defined clades. We discuss a scenario of a possible Chloromonas split and revision.